Virality Modeling and Analysis - HOANG, Tuan Anh (Institutional Knowledge at Singapore Management University, 2011)
Virality is a virus-like behavior that allows a piece of information to widely and quickly diffuse within the network of adopters through word of mouth. It is about how easy users propagate information to their friends and friends of friends by means of diffusion. While virality of information has several interesting applications, there are much research to be conducted on virality. These areas of research include understanding the mechanism of virality, modeling the virality both qualitatively and quantitatively, and applying virality to applications such as marketing, event detection, and others. In this paper, we survey existing works on quantitative models for virality and the relationship between virality and other behaviors. Through the survey, we hope to offer common framework to study topis related to information virality.